C—H⋯π packing interactions in 2-[5,5-bis(4-benzyloxyphenyl)-3-cyano-4-methyl-2,5-dihydrofuran-2-ylidene]malononitrile - Gainsford, Graeme J. (International Union of Crystallography, 2011)
The title molecule, C(35)H(25)N(3)O(3), packs utilizing C—H⋯π attractive interactions causing the identical 4-benzyloxyphenyl groups to pack with different conformational angles. This difference is consistent with the variable interplanar dihedral angles found in closely related structures.